Lar doce lar? Um estudo sobre afetividade de idosos residentes em instituições de longa permanência em Fortaleza - Vieira, Ana Caroline Costa (2012)
The main purpose of this study was to investigate the affection of the elderly at Long Term Institutions in the city of Fortaleza - CE, which are considered dwelling places for those who live there. We verified issues such as the current public policies; housing conditions relate to the level of satisfaction of elderly residents and assess their processes of space appropriation and its relation to the aging. In order to have an overview of the Long Term Institutions distribution, in Fortaleza, a total of 21 elderly people distributed in six institutions were part of our field research, one from each Regional Executive Secretary – RES, where the city is divided. As a theoretical framework we had Environmental Psychology and Social Psychology, its methods and techniques such as focus groups, personal interviews, field diary and the instrument to generate affective maps as a method to seize emotions. Through the images of pleasantness and belonging generated we could visualize positive feelings and qualities of residents, revealing a positive esteem about the place. Regarding the categories of belonging as survival and belonging to the past we recorded feelings and qualities that weakened the person, which triggers a negative esteem of residents in relation to LTCF. Seeking to contemplate these goals we realize that, despite the Brazilian population being in full process of aging, the current society is unprepared to deal with this issue. The existing public policies are very recent and still under implementation. Governmental entities which should help and support the development of institutions such as Long Term Care Facilities for the elderly (LTCF) are only with the role of charge, prosecute and fine. We realize that these elderly residents are disadvantaged in public policy and, moreover, they have no support from family and even society in general.